Cross-Sectional Study of Varicella Zoster Virus Immunity in Healthy Korean Children Assessed by Glycoprotein Enzyme-Linked Immunosorbent Assay and Fluorescent Antibody to Membrane Antigen Test - Yunhwa Kim; Ji-Young Hwang; Kyung-Min Lee; Eunsil Lee; Hosun Park (Vaccines, 2021)
The prevalence of varicella is especially high among children in the age group of 4–6 years in South Korea, regardless of vaccination. We investigated the immune status of healthy children enrolled in day-care centers and compared pre- and post-vaccination immunity. Antibody titers were measured using a glycoprotein enzyme-linked immunosorbent assay (gpEIA) kit, and the seroconversion rate was assessed using a fluorescent antibody to membrane antigen (FAMA) test. Among 541 vaccinated children, 109 (20.1%) had breakthrough varicella. However, 13 (72.2%) of the 18 unvaccinated children had a history of varicella. The gpEIA geometric mean titers (GMTs) of pre- and 5 weeks post-vaccination in 1-year-old children were 14.7 and 72 mIU/mL, respectively, and the FAMA seroconversion rate was 91.1%. The gpEIA GMTs of 2-, 3-, 4-, 5-, and 6-year-old children were 104.1, 133.8, 223.5, 364.1, and 353.0 mIU/mL, respectively. Even though the gpEIA GMT increased with age, the pattern of gpEIA titer distribution in 4- to 6-year-old vaccinees without varicella history represented both waning immunity and natural boosting immunity. These results suggest that some vaccinees are vulnerable to varicella infection. Therefore, it is necessary to consider a two-dose varicella vaccine regimen in South Korea.